PERILAKU SOSIAL ANAK TERLANTAR DALAM POLA PENGASUHAN LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) DI KABUPATEN LUMAJANG - Adhania, Lhery Swara Oktaf (Universitas Dr. Soetomo, 2019)
Child is the next generation in sustainable development. Development requires child as an asset of the nation. Qualified child is a child whose basic needs are met, not a waif unmet basic needs. everal factors make a neglected children. Neglected children tend to have behavior that is incompatible with the norms that exist in society because of parenting are in various limitations. This study aims to determine the behavior of neglected children and the factors behind the existence of abandoned children in LKSA Kurnia Bangsa Lumajang. This study uses descriptive qualitative research approach, the method of data collection through direct observation of the behavior of abandoned children in LKSA Kurnia Nation is supported by interviews with informants and documentation. The behavior of neglected children in LKSA Kurnia Bangsa Lumajang shown by the attitude and actions that deviated (not in accordance with the norms prevailing in society) and caregivers decision LKSA Kurnia Bangsa Lumajang in implementing family parenting, giving reward and punishment, the routine application in daily activities. Factors behind the existence of abandoned children in LKSA Kurnia Bangsa Lumajang, is the environment / parenting, education and intellectual conditions, economic conditions, the condition of the parents (single / full), or the role of government policy.